2013
DOI: 10.1177/0284185113492971
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative analysis of early-stage Alzheimer’s disease and normal aging with automatic segmentation technique in subcortical gray matter structures: a multicenter in vivo MRI volumetric and DTI study

Abstract: Pathological changes takes place in the hippocampus and other subcortical gray matter structures in early-stage AD. Diffusive imaging has great diagnostic significance in early-stage AD. The combination of both imaging modalities can lead to better discrimination between early-stage AD and normal aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…The mean diffusivity (MD), which represents the mean magnitude of water diffusivity, is used to evaluate GM tissue density (Li et al, 2013) with the lower the MD, the more integral the GM.…”
Section: Methodsmentioning
confidence: 99%
“…The mean diffusivity (MD), which represents the mean magnitude of water diffusivity, is used to evaluate GM tissue density (Li et al, 2013) with the lower the MD, the more integral the GM.…”
Section: Methodsmentioning
confidence: 99%
“…Among these brain regions, the number of senile plaques has been reported to be the highest in amygdala (Arriagada et al, 1992). Accordingly, a recent diffusion-tensor imaging study has revealed significant decrease in the relative volume of amygdale in early stage AD subjects (Li et al, 2013). The amygdala has long been known to be vulnerable to Alzheimer-type pathology (Hopper and Vogel, 1976), and it has been described as one of earliest locations to develop Alzheimer pathology in Down syndrome (Mann et al, 1986).…”
Section: Aβ and Excitatory Neurotransmissionmentioning
confidence: 99%
“…For example, the effects of brain injury may be detected sooner with diffusion scans before conventional MRI (Neil, et al., 2002; Sundgren, et al, 2004). A number of studies have examined variation in hippocampus MD in studies of memory (den Heijer, et al, 2012; Piras, et al, 2010), MCI, and AD (Kantarci, et al, 2005) (Cherubini, et al, 2010; Fellgiebel, et al, 2006; Li, et al, 2013b). Brueggen et al (Brueggen, et al, 2015) have recently shown that hippocampus volume is superior to MD when predicting individuals who convert from MCI to AD.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (Li, et al, 2013a; Li, et al, 2013b) have shown that a combination of volume and MD assessed across subcortical gray matter structures, including the hippocampus, can better discriminate early-stage AD from normal subjects. Future analyses may include latent class analysis (Lazarsfeld and Henry, 1968), or factor mixture models (Everitt, 1988) that integrate individual differences in both volume and MD across all seven subcortical ROIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation